Distribution Of Phosphatases, Oxidoreductases And Esterases In Sublingual Salivary Gland Of Buffalo During Neonatal Development (Applied Biological Research, 2015)
The present study was aimed to elucidate the distribution of various  enzymes in sublingual salivary gland of neonatal buffalo (n = 10),  ranging from 1 to 3 months age, and correlate these enzyme systems  with the secretory activity of gland. At 1 month age, a uniform moderate  to strong positive diffused granular alkaline phosphatase activity was  observed in serous acini and ductal epithelium. A moderate positive  glucose-6-phosphatase and succinic dehydrogenase activity was seen  close to the basement membrane. At 2 months age, glutamic dehydro genase showed moderate activity in basal portions of serous acinar cells,  while succinic dehydrogenase activity was strong, granular and evenly  distributed in basement membrane of serous cells. Weak activity of  monoamine oxidase and moderate non-specific esterase activity was  seen. At 3 months age, alkaline phosphatase showed strong positive  perinuclear activity in acinar cells, while glucose-6-phosphatase showed  a moderate to strong activity in acinar cells and in ductal epithelium. Moderate to strong positive non-specific esterase activity was localized  in nerve fibres of intralobular and interlobular connective tissues.  Glucose-6-phosphate dehydrogenase and nicotinamide adenine  dinucleotide diaphorase showed strong positive granular activity in  basement membrane of serous acinar cells and ducts. The high basal  activities of oxidoreductases were because of basal mitochondria and  were associated with high energy production to meet the energy
Keywords: Buffalo; histoenzymic; neonates; sublingual salivary gland